2011
DOI: 10.1016/j.jcrs.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

One million cataract surgeries: Swedish National Cataract Register 1992–2009

Abstract: This review summarizes data collected by the Swedish National Cataract Register, which now contains data pertaining to more than a million cataract surgery procedures, representing 95.6% of the surgeries performed in Sweden during 1992-2009. During this period, the rate of cataract surgery rose from 4.47 to 9.00 per 1000 inhabitants. The mean patient age increased until 1999 but has slowly decreased since then. Preoperative visual acuity has risen steadily. The distribution between the sexes was stable until 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
209
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(239 citation statements)
references
References 18 publications
21
209
2
7
Order By: Relevance
“…Other studies also noted a difference in surgical rate by sex. The proportion of women who underwent cataract extraction was 61% in Sweden, and 59% in France, and it was also significantly higher than in men in Minnesota [6,7,13]. Globally, women have higher rates of blindness and moderate and severe visual impairment (MSVI) caused by cataract compared with men, and sex inequity in cataract surgery still persists in low-and middle-income countries, where men are 1.71 times more likely to have cataract surgery than women [2].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies also noted a difference in surgical rate by sex. The proportion of women who underwent cataract extraction was 61% in Sweden, and 59% in France, and it was also significantly higher than in men in Minnesota [6,7,13]. Globally, women have higher rates of blindness and moderate and severe visual impairment (MSVI) caused by cataract compared with men, and sex inequity in cataract surgery still persists in low-and middle-income countries, where men are 1.71 times more likely to have cataract surgery than women [2].…”
Section: Resultsmentioning
confidence: 88%
“…However, reports on the incidence of cataract surgery based on national basis are limited. In 2011, Behndig et al [6] reported one million of cataract surgeries in Swedish National Cataract Register from 1992 to 2009. In 2015, Daien et al [7] reported the incidence of cataract surgery in France from 2009 to 2012 was 2.7 million cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has different subtypes such as A, B, C, D, etc. Among those subtypes, PDGF-α is the most widely distributed and has the strongest biological effect because it can combine with the target cell PDGFR directly and induce downstream signaling pathways such as the PI3K/Akt, RAS-GAP, and ERK1/2 pathways, with corresponding biological effects (Behndig et al, 2011). Though the PDGF-PDGFR combination has a significant effect on regulating cell proliferation and division, this regulation is strictly controlled in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, millions of people undergo cataract and refractive surgery with intraocular lens (IOL) implantation. The incidence of cataract surgery with IOL implantation as the most commonly performed surgery is still increasing (8,9).…”
Section: Introductionmentioning
confidence: 99%